Culture and Antibiotic Sensitivity of Bacterial pathogens responsible for Post Caesarean Wound Infection in a Tertiary Hospital - Banu, Mahbuba Akhter; Nargis, S F; Sin, Md Mohim Ibn; Pervin, Murshida; Rahman, Md Shahinur; Hossain, Mosharraf; Rahman, Mohammad Mizanoor (Journal of Dhaka National Medical College & Hospital, 2018)
The objective of this study was to find out the most common bacterial pathogens responsible for post-caesarean wound infection and to determine their antibiotic sensitivity profile. This descriptive cross sectional study was carried out in Obstetrics & Gynaecology Department of Sir Salimullah Medical College & Mitford Hospital from September 2016 to February 2017. 50 admitted patients experienced post-caesarean wound infections and were enrolled in this study. Mean age of study patients was 24.24 years ± 4.39 SD, ranges 17-36 years, 60.0% of them were literate and 40.0% respondents came from lower middle class society. 68.0% respondents were multiparous and 48.0% had regular antenatal check-up. Anemia, hypertension and diabetes mellitus were associated in 54.0%, 18.0% and 6.0% respectively. Rupture of membrane and fetal distress were found in 52.0% and 32.0% cases respectively. In 40.0% cases no growth of organism took place. Growth of Staphylococcus aureus was noticed as predominant organism (28.0%). Pseudomonas, Acinetobacter, E. coli, Klebsiella and Staphylococcus epidermidis were found in 10.0%, 6.0%, 6.0%, 6.0% and 4.0% respectively. S. aureus was sensitive to meropenem (50.0%), imipenem (42.8% ), cefuroxime, doxycycline and amikacin (28.5%). Pseudomonas spp. was sensitive to imipenem (80.0%), meropenem and amikacin (60.0%). Acinetobacter showed 100.0% sensitivity to imipenem followed by piperacillin and meropenem (66.6%). Klebsiella was sensitive to imipenem and amikacin (66.6%). E. coli was sensitive to imipenem (66.6%), meropenem and cefuroxime (33.3%). S. epidermidis was 100.0% sensitive to meropenem followed by doxycycline and imipenem (50%). This study concludes that there is an alarming increasing of wound infections caused by antibiotic-resistant bacteria. Staphylococcus aureus is the commonly responsible organism. Particularly, Pseudomonas and E. coli resistance to third generation cephalosporins are the real threats to control hospital acquired infection. J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 38-43